2001
DOI: 10.1124/mol.59.5.1022
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Functional Role of Conserved Arginine and Lysine Residues in Transmembrane Domains of the Murine Reduced Folate Carrier

Abstract: The reduced folate carrier (RFC1) plays a major role in the delivery of folates into mammalian cells. RFC1 is an anion exchanger with seven conserved positively charged amino acid residues within 12 predicted transmembrane domains. This article explores the role of these residues in transport function by the development of cell lines in which arginines and lysines in RFC1 were replaced with leucine by site-directed mutagenesis. Three cell lines transfected with R131L, R155L, or R366L all lacked activity, despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…Ser309Phe (eighth TMD) and Glu404Leu (11th TMD) mutations also produced changes in anion sensitivity. Influx was independent of chloride over a broad range of chloride concentrations with a simulatory effect below 50 mm (Zhao et al, 1999a;Sharina et al, 2001). …”
Section: Resistance Associated With Impaired Rfc-mediated Transportmentioning
confidence: 98%
“…Ser309Phe (eighth TMD) and Glu404Leu (11th TMD) mutations also produced changes in anion sensitivity. Influx was independent of chloride over a broad range of chloride concentrations with a simulatory effect below 50 mm (Zhao et al, 1999a;Sharina et al, 2001). …”
Section: Resistance Associated With Impaired Rfc-mediated Transportmentioning
confidence: 98%
“…The TMD2 exofacial loop boundary region has been slightly modified from a previous report (30) based on biotin maleimide and stibenedisulfonate maleimide labeling results for the hamster (37) and human (data not shown) transporters as described in the text. Structurally or functionally important amino acids, as determined from published mutagenesis studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), are shown as red circles. Deletion of residues 204 -217 was previously found (14) to abolish transport by hRFC.…”
Section: Expression and Function Of Single Cysteine-substituted Hrfc mentioning
confidence: 99%
“…Replacement of Arg-133 in hRFC (with Glu, His, or Leu) or Arg-373 in hamster RFC (with His, Gln, Asn, or Ala) or substitution of leucine at the homologous positions in murine RFC (Arg-131 and Arg-373, respectively) significantly inhibited Mtx transport activity (20,23,26). However, replacement of arginine at these positions with a positively charged lysine was reasonably well tolerated (20,26).…”
Section: Expression and Function Of Single Cysteine-substituted Hrfc mentioning
confidence: 99%
See 1 more Smart Citation
“…However, of the 33 amino acids that have been identified as important for Mtx transport by RFC1 [14][15][16][17][18][19] only Ser 317 was exchanged for an alanine in rat MTX-1 (Fig. 1).…”
Section: Sequence Similaritymentioning
confidence: 99%